Self-palpation Feedback for Abdominal Hollowing Exercise - Young-kyun Kim; Min-ra Choi; Seong-jun Kim; Ki-kwang Lee; Hye-ree Kim (Asian Society of Kinesiology, 2018)
PURPOSE The purpose of this study was to investigate abdominal muscles' thickness change during abdominal hollowing with self-palpation feedback. METHODS Twenty six healthy males participated in this study. Subjects were instructed how to perform AHE on hook-lying position. Ultrasound images (transverse abdominis (TA), internal oblique (IO), external oblique (EO)) were measured during resting and AHE using self-palpation feedback or pressure biofeedback. RESULTS TA thickness increased significantly with both self-palpation feedback and pressure biofeedback groups (p<.05). In TA, the control group showed more increased thickness than the experimental group. However, there was no interaction between AHE and using pressure biofeedback in IO and EO. Also, all subjects's muscle thickness of IO were increased (p<.01) and EO were decreased (p<.05) significantly. CONCLUSIONS Self-palpation feedback during AHE is useful to perform AHE. Therefore self palpation feedback is a simple method to provide feedback when ultrasound and biofeedback equipment are no available.